KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS VIII DITINJAU DARI KECEMASAN MATEMATIS PADA PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA VISUAL - anggita rahma ristayanti; iwan junaedi (Universitas Islam Nusantara, 2021)
The purpose of this study was to determine the effectiveness of learning teams games tournament assisted by visual media and to describe students' mathematical reasoning abilities in terms of mathematical anxiety. This research method is a mix method. This research was conducted at SMP N 23 Semarang with 30 students of class VIII G as the experimental class and 30 students of class VIII H as the control class. Data were collected by using a written test technique and a mathematical anxiety scale. The results of this study indicate that the TGT model is effective for improving students' mathematical reasoning abilities and students' mathematical reasoning abilities in terms of mathematical anxiety, namely (1) Students with high mathematical anxiety have varied abilities, KMT students with category I mathematical reasoning abilities master all indicators, students KMT with category II mathematical reasoning abilities lacked mastery over the indicators of submitting conjectures, KMT students with category III mathematical reasoning abilities did not master all indicators, (2) Students with moderate mathematical anxiety had varied abilities, KMS students with category I mathematical reasoning abilities mastered all indicators, KMS students with category II mathematical reasoning abilities lacked mastery of indicators in proposing conjectures and drawing conclusions, KMS students with category III mathematical reasoning abilities only mastered indicators of finding patterns to make generalizations (3) Students with anxiety low mathematical scores have varied abilities, KMR students with category I mathematical reasoning abilities master all indicators, KMR students with category II mathematical reasoning abilities do not master the indicators of proposing conjectures, KMR students with category III mathematical reasoning abilities only master indicators of finding patterns to make generalizations.